Filter for Intermodulation Distortion Measurement of Audio Power Amplifiers - Puidokas, V.; Marcinkevicius, A. J. (Elektronika ir Elektrotechnika, 2011)
The proposed technique enables measurement of the intermodulation distortions with cheap lower dynamic range (10÷14 or even 8 bit) analyzers using modified Twin-T filter. The idea of the modification is based on the separation of the active and passive filter parts, with location firstly of the passive parts with subsequent active parts. The prototype of the filter was developed for experimental investigation. The both simulation and experimental results confirm that the separation of passive and active parts of the filter give expected results. Ill. 9, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.695